A DC Inrush Current Minimisation Method using Modified Z-source Inverter in Adjustable Speed Drives - S. Renukadevi; M. Rathinakumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The adjustable speed drives employ PWM converter – inverter system in order to obtain unity power factor.The DC inrush current in DC link capacitors of the rectifier limits the operation of power devices.Hence, this paper proposes a new approach to reduce the DC inrush current by employing modified Z-source inverter in a Adjustable Speed Drive system. The operating principles, design procedure and simulation results are shown and compared with the conventional Z-Source inverter.